PELAKSANAAN PERALIHAN HAK ATAS TANAH MELALUI PEJABAT PEMBUAT AKTA TANAH SEMENTARA (PPATS) DI NAGARI PASAR BARU, KABUPATEN PESISIR SELATAN: INTEGRASI HUKUM NASIONAL DAN HUKUM ADAT MINANGKABAU - Rahmady, Windy; Gettari, Trie Rahmi; Haryuniati, Krisma; Yusra, Alfajri (Ensiklopedia of Journal, 2025)
Abstract: This study aims to analyze the implementation of land rights transfer through Temporary Land Deed Officials (PPATS) in Nagari Pasar Baru, Pesisir Selatan Regency, and to identify the integration of national law and Minangkabau customary law in this practice. The research method used is a sociological juridical approach with a descriptive qualitative method, utilizing primary data from interviews and observations, as well as secondary data from literature studies. The results show that formal procedures in accordance with Government Regulation No. 24 of 1997 and Minister of Agrarian Affairs/National Land Agency Regulation No. 3 of 1997 are still applied; however, for ulayat land, the consent of the kaum acknowledged by the Nagari Customary Council (Kerapatan Adat Nagari / KAN) is required. The challenges faced include the majority of land being uncertified, low public legal awareness, and the limited number of definitive PPAT officials. This study emphasizes the importance of synergy between PPATS, village apparatus, KAN, and the Land Office to improve legal certainty and protect community rights.Keywords: PPATS, Land rights transfer, Minangkabau customary law, Land law.